2006
DOI: 10.1159/000091416
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Reduction in Left Ventricular Function following Treatment of Non-Hodgkin’s Lymphoma with Chemotherapy and Rituximab, Unrelated to Acute Infusion Reaction

Abstract: We report 3 cases of reduced cardiac function with complications in non-Hodgkin’s lymphoma patients who were treated with rituximab. Patients experienced reduced cardiac functions after the administration of rituximab; there was no evidence of any preceding infusion reactions. Reticulin fiber was observed diffusely in cardiac muscles. Transforming growth factor-β levels were elevated after the administration of rituximab. We believe that continuous elevation of transforming growth factor-β may promote the grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 18 publications
0
21
1
Order By: Relevance
“…Secondly, our case had a coronary angiogram which demonstrated clean coronary artery. Thus, we could confirm the diagnosis of non-ischemic cardiomyopathy, unlike previously reported cases (16). Thirdly, our case study showed the new finding that a reduction in cardiac function can occur early within 48 hours.…”
Section: Discussioncontrasting
confidence: 41%
See 3 more Smart Citations
“…Secondly, our case had a coronary angiogram which demonstrated clean coronary artery. Thus, we could confirm the diagnosis of non-ischemic cardiomyopathy, unlike previously reported cases (16). Thirdly, our case study showed the new finding that a reduction in cardiac function can occur early within 48 hours.…”
Section: Discussioncontrasting
confidence: 41%
“…Kanamori et al (16) reported delayed effect (>2 weeks following rituximab infusion) of reduced LVEF in 3 cases with NHL (Table 1). The prognosis was different in each reported case.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, one patient with dilated cardiomyopathy died after RTX infusion [93] and three cases of reduced cardiac function in non-Hodgkin's lymphoma patients treated with RTX were reported [94]. Other case reports reported a cardiogenic shock in a young patient suffering from thrombotic thrombocytopenic purpura, where HF discharged after therapeutic plasma exchange [95], and a fatal MI in a 60-year-old diabetic patient who received RTX, whereas the baseline echocardiography and electrocardiogram were normal [96].…”
Section: Rituximab May Cause Acute Infusion Reactionsmentioning
confidence: 99%